The Theological-Eschatological Implications of Name Michael in Jude - Javien, Rico Taga (Klabat Theological Review; Vol 1 No 2 (2020): Klabat Theological Review, 2020)
The pastoral epistle of Jude is shrouded with rich theological significance, in spite of its shortness. Theological themes like order of salvation, faith, mission, worship, judgment, great controversy, second coming, and the end of the world, and others are interwoven in the fabric of Jude. It means that Jude starts with protology and ends with climactic and cosmic victorious eschatology, particularly the resurrection of the righteous.             The sudden appearance of Michael, the Archangel heightens the conflict in Jude. Scholars from the different camps admit Jude 9 where Michael appears in contending the devil over the body of Moses, is the most perplexing text in the entire epistle. Jesus Christ eschatological name is: Michael. The name is so significant particularly in the conflict of Moses’ resurrection to glory. Satan by all means struggled to prevent him to be resurrected and taken from his territory, for he claimed Moses belonged to his kingdom because he was a sinner.             In epistle of Jude the great controversy does not end of the temporal life, the physical death but even extended until the day of resurrection. Whenever, Michael is referred to in the Bible, are all in the contexts of intense violence, war, death, hopelessness and resurrection and triumph. Michael is the heavenly warrior who defends victoriously for His people who will end the great controversy in grandest victory, is indeed the highlight of Jude’s eschatology.     Keywords: Michael; devil; Moses; contending; conflict; struggle; apostasy; the great controversy